Household participation in domestic waste disposal and recycling: an environmental education implication (2010)
This study examined the factors influencing household participation in waste disposal and recycling focusing educational level, location of residence and income. The study was carried out in four Local Governments Areas in Oyo Metropolitan Area, namely Atiba, Oyo East, Oyo West and Afijio. Three research questions were formulated to provide data for this study. 192 household were sampled for this study. The data collected were analyzed using frequency counts and simple percentages. The findings revealed that there is low level of participation of household in waste disposal and recycling as a result of low level of household awareness on environmental implication of proper waste management. Also, revealed low household participation in waste sorting, disposal and recycling across educational level, income and location of residence. The findings have environmental implications. Therefore, it was recommended that teaching of environmental education should be promoted not only in school but also in informal ways of educating citizens.